KNOWLEDGE ACCEPTANCE MODEL OF MOOC ONLINE EDUCATION PLATFORM FROM THE PERSPECTIVE OF KNOWLEDGE SHARING - Wang, Yang; Mou, Lanjuan; Luo, Haijiang (Journal of Buddhist Education and Research (JBER), 2023)
In an increasingly competitive environment, knowledge resources play an increasingly important role. "Knowledge has become a key economic resource, and it is the dominant source of competitive advantage, and may even be the only source (Drucker, 1995)." Knowledge sharing and knowledge innovation have now become the core competitiveness of various countries and have been highly valued by the country. In particular, it has a far-reaching impact on the development of colleges and universities. The school is a national knowledge reserve center and a national knowledge strategic resource. Actively exploring the path and mechanism of knowledge sharing in colleges and universities in the way to maximize the effectiveness of knowledge, which is of great significance. At the moment of the epidemic, Internet education has become the most necessary way to learn knowledge. Knowledge sharing is an important prerequisite for knowledge construction and knowledge creation on internet learning platforms. However, the lack of systematic research on the relationship and path of its influencing factors makes it difficult. Reveal the effective knowledge transfer process, which leads to the weakening of the viscosity between the Internet learning platform and the learners, and the unsatisfactory learning quality. On this basis, this article takes college students from a university in western China as the research object, and takes the representative MOOC online education platform in the internet learning platform as an example, using the technology acceptance model(TAM) to analyze the relationship between various factors of the internet education platform, using SPSS software to carry out correlation, regression and other analysis methods on the 152 questionnaires recovered, and finally deduce the knowledge acceptance model of college internet education platform. It provides an effective reference for learners to better receive knowledge from the Internet platform, effectively guides the development direction of Internet education, promotes the sharing of knowledge resources, enhances the ability of colleges and universities to radiate science and technology to the outside world, and promotes the coordination and innovation of knowledge. And it has important reference value for professional interaction and compound talent training.